SUSTAINABLE DEVELOPMENT GOALS IN THE TOURISM INDUSTRY (CASE STUDY OF THE HOSPITALITY INDUSTRY IN CENTRAL KALIMANTAN, INDONESIA) - Rhama, Bhayu; Setiawan, Ferry (UI Scholars Hub, 2022)
Tourism is one way to achieve the Sustainable Development Goals (SDGs) but there has been no evaluation of whether the accommodation industry which has a consumptive character plays a role in creating sustainable development. Hotel accommodation that has a global network cannot avoid the consumptive aspect that emphasizes luxury so that it exploits resources such as electricity and is not environmentally friendly. The study uses a qualitative approach to evaluate the theory of consumption and further development using two hotels with global networks in Central Kalimantan focusing on the environment because of its proximity to the White and Half-White National Challenges Park to demonstrate the commitment of the global hotel industry to the SDGs. The results show that tourism through the accommodation industry sector cannot be separated from consumptive behavior so that it is only in the early stages of supporting sustainable development goals and directly at points 6, 7, 13 and 15.